Neuroactive steroids for the treatment of status epilepticus. (3rd September 2013) - Rogawski, Michael A.; Loya, Carlos M.; Reddy, Kiran; Zolkowska, Dorota; Lossin, Christoph
Summary: Benzodiazepines are the current first‐line standard‐of‐care treatment for status epilepticus but fail to terminate seizures in about one third of cases. Synaptic GABAA receptors, which mediate phasic inhibition in central circuits, are the molecular target of benzodiazepines. As status epilepticus progresses, these receptors are internalized and become functionally inactivated, conferring benzodiazepine resistance, which is believed to be a major cause of treatment failure. GABAA receptor positive allosteric modulator neuroactive steroids, such as allopregnanolone, also potentiate synaptic GABAA receptors, but in addition they enhance extrasynaptic GABAA receptors that mediate tonic inhibition. Extrasynaptic GABAA receptors are not internalized, and desensitization of these receptors does not occur during continuous seizures in status epilepticus models. Here we review the broad‐spectrum antiseizure activity of allopregnanolone in animal seizure models and the evidence for its activity in models of status epilepticus. We also demonstrate that allopregnanolone inhibits ongoing behavioral and electrographic seizures in a model of status epilepticus, even when there is benzodiazepine resistance. Parenteral allopregnanolone may provide an improved treatment for refractory status epilepticus.